Evaluation of Oral Cannabinoid-Containing Medications for the Management of Interferon and Ribavirin-Induced Anorexia, Nausea and Weight Loss in Patients Treated for Chronic Hepatitis C Virus. (2008) - Costiniuk, Cecilia T; Mills, Edward; Cooper, Curtis L
Abstract : OBJECTIVES: The systemic and cognitive side effects of hepatitis C virus (HCV) therapy may be incapacitating, necessitating dose reductions or abandonment of therapy. Oral cannabinoid-containing medications (OCs) ameliorate chemotherapy-induced nausea and vomiting, as well as AIDS wasting syndrome. The efficacy of OCs in managing HCV treatment-related side effects is unknown. METHODS: All patients who initiated interferon-ribavirin therapy at The Ottawa Hospital Viral Hepatitis Clinic (Ottawa, Ontario) between August 2003 and January 2007 were identified using a computerized clinical database. The baseline characteristics of OC recipients were compared with those of nonrecipients. The treatment-related side effect response to OC was assessed by χ 2 analysis. The key therapeutic outcomes related to weight, interferon dose reduction and treatment outcomes were assessed by Student's t test and χ 2 analysis. RESULTS: Twenty-five of 191 patients (13%) initiated OC use. Recipients had similar characteristics to nonrecipients, aside from prior marijuana smoking history (24% versus 10%, respectively; P=0.04). The median time to OC initiation was seven weeks. The most common indications for initiation of OC were anorexia (72%) and nausea (32%). Sixty-four per cent of all patients who received OC experienced subjective improvement in symptoms. The median weight loss before OC initiation was 4.5 kg. A trend toward greater median weight loss was noted at week 4 in patients eventually initiating OC use (−1.4 kg), compared with those who did not (−1.0 kg). Weight loss stabilized one month after OC initiation (median 0.5 kg additional loss). Interferon dose reductions were rare and did not differ by OC use (8% of OC recipients versus 5% of nonrecipients). The proportions of patients completing a full course of HCV therapy and achieving a sustained virological response were greater in OC recipients. CONCLUSIONS: The present retrospective cohort analysis found that OC use is often effective in managing HCV treatment-related symptoms that contribute to weight loss, and may stabilize weight decline once initiated.